The Analyses of Cetacean Virus-Responsive Genes Reveal Evolutionary Marks in Mucosal Immunity-Associated Genes - Oksung Chung; Ye-Eun Jung; Kyeong Won Lee; Young Jun An; Jungeun Kim; Yoo-Rim Roh; Jong Bhak; Kiejung Park; Jessica A. Weber; Jaehun Cheong; Sun-Shin Cha; Jung-Hyun Lee; et al. (Biochemical Genetics, 2022)
Viruses are the most common and abundant organisms in the marine environment. To better understand how cetaceans have adapted to this virus-rich environment, we compared cetacean virus-responsive genes to those from terrestrial mammals. We identified virus-responsive gene sequences in seven species of cetaceans, which we compared with orthologous sequences in seven terrestrial mammals. As a result of evolution analysis using the branch model and the branch-site model, 21 genes were selected using at least one model. IFN-ε, an antiviral cytokine expressed at mucous membranes, and its receptor IFNAR1 contain cetacean-specific amino acid substitutions that might change the interaction between the two proteins and lead to regulation of the immune system against viruses. Cetacean-specific amino acid substitutions in IL-6, IL-27, and the signal transducer and activator of transcription (STAT)1 are also predicted to alter the mucosal immune response of cetaceans. Since mucosal membranes are the first line of defense against the external environment and are involved in immune tolerance, our analysis of cetacean virus-responsive genes suggests that genes with cetacean-specific mutations in mucosal immunity-related genes play an important role in the protection and/or regulation of immune responses against viruses.